Parameters of fuel jet extraction in video - Eskov, Alexsander; Svistula, Andrey; Dolmatov, Alexey (Transport, 2005)
The statistical rating of the image of a fuel jet allows to allocate the zones with homogeneous brightness, to define the distribution of masses and the concentration in a fuel jet and to look after their dynamics. In the research the coding with the usage of Byeses’s definition of the aposteriory probability of the presence of the given brightness in the image is described. The bright zones of a fuel jet in a diesel engine will give to the conclusion how the fuel is distributed in the engine combustion camera. First Published Online: 27 Oct 2010